Balancing Work–family Life in Academia: The Power of Time. Issue 3 (4th August 2011) - Rafnsdóttir, Gudbjörg Linda; Heijstra, Thamar M.
<x xml:space="preserve">Abstract</x> In the article we analyse the structuring of time among academic employees in Iceland, how they organize and reconcile their work and family life and whether gender is a defining factor in this context. Our analysis shows clear gender differences in time use. Although flexible working hours help academic parents to organize their working day and fulfil the ever‐changing needs of family members, the women, rather than men interviewed, seem to be stuck with the responsibility of domestic and caring issues because of this very same flexibility. It seems to remove, for more women than for men, the possibility of going home early or not being on call. The flexibility and the gendered time use seem thus to reproduce traditional power relations between women and men and the gender segregated division in the homes.